You are on page 1of 11

Γ

Γ(x) = exp(t)t x1 dt

0

x > 0

 Γ(n + 1) = n! n ∈ Z + xΓ(x) = Γ(x + 1) x > 0

Γ(z) C

0, 1, 2,

...

n

(1) n

n!

Γ(z) =

exp (γz)

z

n=1

1 +

n z 1

exp(z/n)

Z

R

R

+

R

n

n

R n

f f

f f f S S

z S z

f M(Ω)

z 0 C f(z) =

1

zz 0 z = C−{z 0 } n N

C − {z 0 } z 0 n f(z)

C f M(Ω)

1

f(z) = p(z) p(z)

C p(z)

x > 0

Γ(x) = 1 (log(t)) x1 dt

0

x > 1 |t z | = t Re(z) Γ(z) Re(z) > 0

Γ(z) = t z1 e t dt

0

Γ(z) = 2 t 2z1 e t 2 dt

0

u = log(t) u 2 = log(t)

Γ

0 < A <

Γ A (z) = A t z1 e t dt

0

Γ A (z)

Γ A Γ

A → ∞

Re(z) > 0

Γ(z + 1) = zΓ(z)

n! = Γ(n + 1) n = 0, 1, 2, ...

Re(z) > 0

Γ(z) =

Γ(z + 1)

z

Γ(z + 1) Re(z) > 1 Γ(1)

= 0 Γ

Re(z) > 1

Γ

Re(z) > 2 1 0

h(z) =

1

z

n=1

e z/n 1 +

n 1

z

N Z +

h N (z + 1)

h N (z) =

1

z

N

n=1

e z/n 1 +

n 1

z

=

=

=

=

1

z + 1

N

n=1

e (z+1)/n 1 +

z + 1

n

1

1

z

+

1

exp

N

n=1

1/n e z/n

n

z + 1 + n

z

+ N exp

z + 1

N

n=1

1/n

1

z e z/n

n

z + n

z

N

+ N exp log(N) +

z + 1

N

n=1

1/n h N (z)

N

log(N)+ n=1 1/n γ

N → ∞

n (log(n + 1) log(n) =

1

n

n+1

1

n

1

t

dt <

n

n+1

1

n + 1 dt

1

n

0 < γ < 1 N → ∞

h(z + 1) = e γ zh(z)

g(z) =

e γz

z

n=1

e z/n 1 +

n 1

z

g

 g(z + 1) = zg(z) g Γ(z + 1) = zΓ(z) Γ(1) = 1 Γ f(z) = Γ(z) g(z)

f(z) f(z)

f(z) = 1 Γ = g f(z + 1) = f(z)

|f(x + iy)| 1 x 2 |t x+iy | = t x

t > 0 x, y R

|Γ(x + iy)| ≤ Γ(x) c

 1 ≤ x ≤ 2 z = x + iy x > 0

x + log |1 + z| ≤ log (1 + |z| 2 ) 1/2

2x + log((1 + x) 2 + y 2 ) log((1 + x 2 + y 2 )

1 a < b log(a) b a

g z = x + iy x > 0

g(z) |z|/2πe γx e π|z|/2

1

 1 |g(z)| = |z|e γx ∞ 1 + |z| 2 n 2 π|z|

n=1

n=1

e x/n

1 +

z

n

≤ |z|e γx

n=1

1 + |z| 2

n 2

1/2

= i sin(|z|) = (e π|z| e π|z| )/2 < e π|z| /2

z

Γ(z) =

e γz

z

n=1

e z/n 1 +

n 1

z

z

Γ(z)Γ(1 z) =

π

sin(πz)

z C

 Γ(z) = l´ım n!n z n→∞ z(z + 1) .(z + n) n e z(−γ+ j=1 1/j) n Γ(z) l´ım n→∞ 1 + z = z j j=1 e z log(n) n = l´ım j z + j n→∞ z j=1 = l´ım n→∞ n!n z z(z + 1) .(z + n)

1

λ C \ (−∞, 0] e λ = Γ λ(x) R

x (0, )

λ(z + 1) = λ(z) + log(z)

0 < a < π c

|λ (z)| ≤ c/|z|

z S a S a = {re it : r > 0, a < t < π} |z| ≥ 2

λ (z) =

n=0

1

(z + n) 2

c > 0

|z + n| ≥ cn

z ∈ § a

n > 0 N

|z + n| ≥ |z|/2

Z + N ≤ |z|/2 < N + 1 0 n ≤ |z|/2

N

n=N+1

1

|z + n| 2 4

N+1

|z| 2 = 4 N + 1

1

|z|

2

c

|z|

N

n=N+1

1

|z + n| 2 c

N+1

1

n

2

c

N

1

2 dt =

t

c

N

c

|z|

β R

1

0

λ(z + t)dt = z log(z) z + β

z C \ (−∞, 0]

1

F(z) =

0

λ(z + t)dt F

F (z) = λ(z + 1) λ(z) = log(z)

z log(z) z

β z (0, ) β R

0 < a < π

λ(z 1) ((z + 1/2) log(z + 1/2) (z + 1/2) + β) 0

z → ∞ S a

z z + 1/2

1/2

1/2 λ(z + 1 + t)dt

=

=

1 λ(z + 1/2 + t)dt

0

(z + 1/2) log(z + 1/2) (z + 1/2) + β

1/2

λ(z + 1) 1/2 λ(z + 1 + t) 0

f : (0, ) (0, ) f(x +

1) = xf(x) f(1) = 1 log(f) f(x) = Γ(x) x > 0

n N

f(x + n) = x(x + 1)

. .

.(x + n 1)f(x);

f(n + 1) = n! f(x + 1) = f(x) f(1) = 1

x (0, 1) log(f)

f(xa + (1 x)b) f(a) x f(b) 1x

a, b > 0 n N

x + n = (1 x)n + x(n + 1),

log

 x(x − 1) .(x + n − 1)f(x) = f(x + n) ≤ f(n) 1−x f(n + 1) x = ((n − 1)!) 1−x (n!) = n x (n − 1)! n + 1 = x(x + n) + (1 − x)(x + n + 1) n! = f(n + 1) ≤ f(x + n) x f(x + n + 1) 1−x = (x + n) 1−x x(x + 1) .(x + n − 1)f(x)

n!n

x

.(x + n) x + n

n

x(x + 1)

x

f(x)

n!n

x

.(x + n) x + n

n

x(x + 1)

f(x) = Γ(x)